Re-examining the Validity of the Full-Range Leadership Models - Gebremariam, Goitom Woldelibanos; Mulu, Yalew Endawoke (Bahir Dar Journal of Education, 2018)
Ethiopia converges with other cultural groups on certain values and diverges on some others (Hofstede, 2001). As a result of the cultural divergence, it was hypothesized that the psychometric properties of the Multifactor Leadership Questionnaire and the leadership models are likely to vary in the Ethiopian context. For that purpose, six hundred twenty seven academic staff from three public universities located in the National Regional State of Tigray were selected using stratified sampling. The participants rated their immediate leader’s leadership practices using the Multifactor Leadership Questionnaire trimmed by Avolio, Bass, and Jung (1999). The participants also rated their own organizational commitment using the Meyer, Allen, and Smith (1993) revised Organizational Commitment Scale. Confirmatory factor analysis of the eight competing models showed that the data fit best to a nine-factor model. Correlational analysis indicated that the five components of transformational leadership, contingent reward, and management-by-exception active had strong relationships (r > .7) with each other, which indicates the existence of higherorder factors. The search for higher-order factors again produced a two-factor leadership model (active and passive) with a good fit. The criterion validity of the nine factors were also tested. Correlational analysis showed that with the exception of active management-by-exception, the other factors showed functional universality as proposed by Bass (1997). Conclusions, implications, limitations, and future research directions were discussed